The global diet: trade and novel infections - Kimball Ann; Hodges Jill R (BMC, 2005)
Abstract Practices designed to meet the demands of global trade can amplify food safety problems. Ever-increasing pressure to churn out more product and better sides of beef has generated processes that compromise existing safety measures. Among the concerns are intensified food production, use of antimicrobials and hormones as growth promoters, and poor sanitary infrastructure in some food producing countries. Accompanying the innovations designed to serve the diversifying global palate are emerging and re-emerging infectious diseases, or "trade-related infections." The joint efforts of international public health and industry are required to effectively address these growing health challenges.